2021
DOI: 10.3390/ani11071982
|View full text |Cite
|
Sign up to set email alerts
|

Bold Frogs or Shy Toads? How Did the COVID-19 Closure of Zoological Organisations Affect Amphibian Activity?

Abstract: Amphibians are an understudied group in the zoo-focussed literature. Whilst commonly housed in specialist exhibits and of real conservation value due to the global extinction crisis, amphibian welfare is not often investigated empirically in zoo settings. The limited research that is available suggests that enclosure design (structure, planting and naturalistic theming) has a positive impact on the time that amphibians will be on show to visitors. However, the categorisation of any “visitor effect” (i.e., infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…These outcomes reflect the diversity of responses to the lockdown identified in a range of taxa by other authors [19,21,28,47]. Common with the only other reptile-based study of the impact of lockdown ( [19]; saltwater crocodiles), the majority of reptile species in this study showed only a small, if any, response to changes in visitors' presence.…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…These outcomes reflect the diversity of responses to the lockdown identified in a range of taxa by other authors [19,21,28,47]. Common with the only other reptile-based study of the impact of lockdown ( [19]; saltwater crocodiles), the majority of reptile species in this study showed only a small, if any, response to changes in visitors' presence.…”
Section: Discussionsupporting
confidence: 73%
“…However, the stronger effects seen in some taxa highlighted that some reptiles may be sensitive to human presence. It is important to note that, like the amphibian study of Boultwood et al [21], we were unable to collect detailed behavioural data reflecting those collected by some other authors for our species [19,47,48] as a result of resource constraints during lockdown, and therefore, some behavioural changes that did not affect activity or visibility may have been undetected. It is important to note that, although we demonstrated effects of visitors on some species, our data did not allow us to attribute this to positive or negative changes in their welfare state.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations